Post-Tsunami Recovery: Issues and Challenges in Sri Lanka - Sisira Jayasuriya; Paul Steele; Dushni Weerakoon (Asian Development Bank Institute (ADBI), 2006)
This is one of the first analytical reports on the major lessons learned from Sri Lanka's experience of the tsunami and the response in the rebuilding phase: Promised external assistance appeared at first to be more than adequate to cover reconstruction costs in full. But problems soon emerged with relief payments, providing credit facilities, distribution of funds, coordination of reconstruction activities, and mismanagement of funds. Progress has been slow, uneven, and concentrated in certain areas, while missing other regions. Poor coordination among domestic and external agencies has emerged as a serious problem, together with the sensitive issue of balancing political considerations and humanitarian assistance to the needy. Some international NGOs' reluctance to cooperate with government institutions, and competitive behavior towards other agencies have hampered coordination and implementation. The modalities of aid spending, including procedures and mechanisms need to be reviewed to improve quick and effective responses. Problems with aid utilization and accountability must be urgently addressed. Practical policy recommendations made in this report include: livelihood related cash payments to households; assistance for rebuilding houses; titles to new houses; buffer zone rules; early warning and disaster management systems; coordination of donor assisted activities and macroeconomic policy issues. Doubtless other tsunami-affected countries could benefit from a similar study by local scholars to reconfirm applicable lessons and to identify home-grown solutions so that something of lasting positive value may yet come out of this appalling tragedy.
hdl:11540/4176
Keywords: 330